Developing AI-Based Educational Animated Videos for Islamic Religious Education in Junior High Schools - Muhammad Rayfansyah; Muhammad Luthfi Hamzah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to develop an Artificial Intelligence (AI)-based educational animated video as a learning medium for Islamic Religious Education (PAI), specifically on the Islamic Cultural History (SKI) topic "Andalusia: The City of Islamic Civilization in the West" for seventh-grade junior high school students, as well as to assess its feasibility and effectiveness in improving student learning outcomes.  Previous studies on PAI learning media have rarely integrated generative AI technologies into animated instructional design. The research employed the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 17 seventh-grade students at SMP Al-Muhajirin Pekanbaru, selected through purposive sampling. A Pre-Experimental Design with One-Group Pretest-Posttest Design was applied. Data were collected using a media expert validation sheet (Likert scale), as well as pre-test and post-test instruments. The media expert validation results indicated a feasibility percentage of 93.13%, categorized as "Highly Feasible". Statistical analysis using the Wilcoxon Signed-Rank Test yielded a Z value of -3.650 with Asymp. Sig. (2-tailed) < 0.001, demonstrating a significant difference between pre-test scores (mean 66.47) and post-test scores (mean 85.88). The average N-Gain Score of 0.6346 (63.46%) falls within the "moderate" and "sufficiently effective" categories. Therefore, the AI-based educational animated video developed in this study is declared feasible and effective for use in PAI learning at the junior high school level.